Asthma and rhinitis in Greek furniture workers. (1st February 2021) - Paraskevaidou, Katerina; Porpodis, Konstantinos; Kontakiotis, Theodoros; Kioumis, Ioannis; Spyratos, Dionisios; Papakosta, Despina
Abstract: Objective: The detection of asthma and rhinitis in furniture workers exposed to chemicals in the area of Thessaloniki Greece and the determination of the most useful tests for diagnosing the above occupational diseases. Methods: Eighty-three workers (76 men), 35 exposed to chemicals (CW), 23 to wood dust (WW), and 25 office workers (OW), serving as controls, filled in a specialized European Community Respiratory Health Survey (ECRHS) questionnaire for asthma and were submitted to clinical evaluation, spirometry, bronchodilation test, PEF computer algorithm OASYS-2, FeNO, skin prick tests (SPTs), rhinomanometry and methacholine inhalation challenge. Working conditions and protective measurements were also recorded. According to the results of all conducted tests, each subject was distributed to a subgroup: (a) normal, (b) asthma, (c) rhinitis, (d) asthma and rhinitis. Comparisons were performed among work groups. Results: The presence of asthma and/or rhinitis was higher among CW and WW compared to OW ( p = 0.004). Significant differences among groups were observed in the questions «better weekend» ( p < 0.034) and "improvement on vacation» ( p < 0.000), in OASYS-2 Score ( p < 0.000), in ABC Score ( p < 0.000), and in methacholine score ( p < 0.022). Rhinomanometry, FeNO, spirometry, and spirometry after bronchodilation had no significant differences among groups. Working conditions, ventilation system, work practice, use and type of mask revealed no significant differences. Conclusion : Asthma and rhinitis are significantly common among CW. Protective measurements used were not adequate to prevent asthma and or work related rhinitis. Early diagnosis might contribute to disease prevention and control.